The role of personality traits in leisure time physical activity during COVID-19 pandemic. (November 2021) - Kekäläinen, Tiia; Sipilä, Sarianna; Saajanaho, Milla; Kokko, Katja
Abstract: The COVID-19 pandemic has affected everyday life, including physical activity behavior. This study examined the role of the five factor model of personality traits on leisure time physical activity during the pandemic in a sample (n = 168) of 61 year-old Finnish men and women, participating in a larger longitudinal study, between April 2020 and April 2021. Frequency of participation and changes in leisure time physical activity were self-reported. Personality traits and facets were assessed with the 181-item NEO-PI. Openness was the only factor positively associated with leisure time physical activity frequency. Participants scoring higher in extraversion (particularly the activity-facet) and lower in openness to values were more likely to report change in their physical activity. In conclusion, individual differences in traits appear to have played a role in physical activity behavior during the pandemic.